2019
DOI: 10.5194/gmd-12-1573-2019
|View full text |Cite
|
Sign up to set email alerts
|

The Beijing Climate Center Climate System Model (BCC-CSM): the main progress from CMIP5 to CMIP6

Abstract: Abstract. The main advancements of the Beijing Climate Center (BCC) climate system model from phase 5 of the Coupled Model Intercomparison Project (CMIP5) to phase 6 (CMIP6) are presented, in terms of physical parameterizations and model performance. BCC-CSM1.1 and BCC-CSM1.1m are the two models involved in CMIP5, whereas BCC-CSM2-MR, BCC-CSM2-HR, and BCC-ESM1.0 are the three models configured for CMIP6. Historical simulations from 1851 to 2014 from BCC-CSM2-MR (CMIP6) and from 1851 to 2005 from BCC-CSM1.1m (C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
185
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 580 publications
(220 citation statements)
references
References 77 publications
1
185
0
Order By: Relevance
“…The present study shows the improvements in the simulation of the EAJ in the CMIP6 models, with an improved description of the intensity and longitudinal location as well as reduced uncertainty. The improvements are likely induced by the improved AOGCMs in the CMIP6, for example, the higher resolutions in the atmosphere and ocean, improved representations of physical processes (Wu et al 2019) and improved representation of aerosols (Wyser et al 2019). However, how the changes in the AOGCMs improve the simulation of the EAJ in the CMIP6 models is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study shows the improvements in the simulation of the EAJ in the CMIP6 models, with an improved description of the intensity and longitudinal location as well as reduced uncertainty. The improvements are likely induced by the improved AOGCMs in the CMIP6, for example, the higher resolutions in the atmosphere and ocean, improved representations of physical processes (Wu et al 2019) and improved representation of aerosols (Wyser et al 2019). However, how the changes in the AOGCMs improve the simulation of the EAJ in the CMIP6 models is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the earlier versions of AOGCMs used in the CMIP5, the CMIP6 models have been improved in many aspects, such as higher resolutions in the atmosphere and ocean, an improved representation of physics (e.g. Wu et al 2019), and improved representation of aerosols (e. g. Wyser et al 2019). Therefore, the output data provide an opportunity to estimate the abilities of these new AOGCMs to simulate the EAJ, which is the motivation for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we use the default horizontal spectral resolution of T42 (approximately 2.8° latitude × 2.8° longitude). The dynamical core and physical processes of the BCC-AGCM3 have been described comprehensively in Wu et al (2008Wu et al ( , 2010 with recent updates documented in Wu et al (2012Wu et al ( , 2019. Wu et al (2019) showed that the BCC-CSM2 (BCC-AGCM3 as the atmospheric model) well captured the global patterns of temperature, precipitation, and atmospheric energy budget.…”
Section: The Atmospheric Model Bcc-agcm3mentioning
confidence: 99%
“…BCC-GEOS-Chem is built on the coupling of the GEOS-Chem chemical module to the BCC Atmospheric General Circulation Model (BCC-AGCM), the atmospheric component of the BCC-CSM2. BCC-CSM2 is a fully coupled global CSM in which the atmosphere, land, ocean, and sea-ice components interact with each other through the exchange of momentum, energy, water, and carbon (Wu et al, 2008(Wu et al, , 2013(Wu et al, , 2019. The earlier version of BCC-CSM (v1.1 and v1.1m) was enrolled in CMIP5 and has been widely applied on weather and climate research (e.g., Wu et al, 2013Wu et al, , 2014Xin et al, 2013;Zhao and He, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation